A business analysis methodology - Bachoo, Avsharn (My University, 2008)
Synopsis Business analysis is defined as the process in which business needs are identified and solutions proposed. This process is regarded as one of the most important parts of systems development because no other part is more difficult to rectify later. However, current business analysis methodologies are inadequate because they are at a too high level and only address portions of the complete business analysis process. In particular, the lack of clear objectives, relevance and outcomes of the phases make business analysis methodologies inadequate. Moreover, activities, techniques and tools not mapped to those phases are also problematic. The aim of this research was to develop a business analysis methodology for business analysts in the South African financial services environment. The intentions were to identify the phases, as well as objectives, relevance and outcomes for each of these phases. Furthermore, this research intended to identify appropriate activities, techniques and tools to address the objectives of each phase of a methodology. This was done by presenting a literature review of previous research relating to business analysis methodologies. For information gathering, 45 participants (comprising of business analysts, project managers, IS managers and CIOs) contributed to this research, 22 of whom were interviewed individually while 23 participated in focus group interviews. The data from each of these methods was analysed independently and did not influence or feed into any of the other methods. Once the individual interviews and focus group interviews had been transcribed, content analysis and analysis within and between interviews (Merriam, 1998; Strauss, 1987) was used to analyse the information gathered independently. The phases of a business analysis methodology identified by the research are the: • feasibility phase; • business case phase; • analysis and design phase; and • post-implementation evaluation phase. Objectives, relevance and outcomes of these phases were also identified. In addition, activities, techniques and tools were mapped to each of these phases.
Keywords: Business analysis; methodology; phases; activities; techniques; tools